Towards an integrated approach to cohesion and coherence in interlingual subtitling - Mubenga, Kajingulu Somwe (Stellenbosch Papers in Linguistics Plus, 2011)
This paper is written from the perspective of systemic functional linguistics (Halliday 1978). In this perspective, a text is a semantic unit that has a particular function and is related to its social system via its context of situation and of culture (Eggins 1994; Halliday and Hasan 1985). These inherent properties of a text hold true for a translated text as well. Since translation is an act of communication, priority is given to functional equivalence (Waard and Nida 1986) and norms (Toury 1995). The aim of this paper is to propose an integrated approach – an approach that combines linguistic and nonlinguistic resources – to cohesion and coherence in interlingual subtitling since this has not yet been done in translation studies. Thus, the paper is purely theoretical in nature. It is divided into four sections. The first section is an introduction to the notions of cohesion and coherence. The second section discusses current theories of cohesion and coherence. The third section reviews various approaches to these notions. In the final section, an integrated approach is proposed as a viable approach to cohesion and coherence in interlingual subtitling. Advantages and implications of this integrated approach are highlighted for further research.